1982
DOI: 10.1093/geronj/37.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Isolating the Age Deficit in Speeded Performance

Abstract: The 'locus' of the age-associated behavioral slowing was investigated with Sternberg's additive-factor method of identifying information processing stages. The factor of adult age was found to interact with manipulations assumed to influence stages concerned with stimulus encoding, internal comparison, and response preparation or execution. Since age appeared to affect each stage of information processing, it was suggested that the age-associated slowing phenomenon is general rather than specific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
81
1
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(95 citation statements)
references
References 0 publications
12
81
1
1
Order By: Relevance
“…Thus, weak signals need to be recognized from a great deal of noise, slowing the process of perception and action, even greater when ID increases. 27,29,30 The findings of the present study seem to give support to the notion that older people are more sensitive to changes in ID since the slope values of the young women' s regression lines were smaller than those of the elderly. 3 Additionally, y-intercepts and r 2 values in the older women groups corroborate reported age-related differences in SATO.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Thus, weak signals need to be recognized from a great deal of noise, slowing the process of perception and action, even greater when ID increases. 27,29,30 The findings of the present study seem to give support to the notion that older people are more sensitive to changes in ID since the slope values of the young women' s regression lines were smaller than those of the elderly. 3 Additionally, y-intercepts and r 2 values in the older women groups corroborate reported age-related differences in SATO.…”
Section: Resultssupporting
confidence: 80%
“…[24][25][26] In addition to the old people' s desire of being perceived as younger than they really are and hence doing the best to be accurate (not fast), aging-related noise contributes to diffuse neuron loss so that the activation of relevant neurons to perform motor tasks is weakened in old people, and, as a result, they tend to take more time to integrate perception and action. [27][28][29][30] …”
Section: Introductionmentioning
confidence: 99%
“…In another experiment, Zacks and Zacks (1993, Experiment 1) used a forced-choice staircase procedure to determine threshold durations for visual search specifically Salthouse & Somberg (1982) 202.6 1.579 1.000 1.579 Salthouse (1994) 675.6 0.962 .989 0.947 Strayer & Kramer (1994) 259.6 1.522 .976 1.468 to preclude the possibility of age differences in timeaccuracy tradeoffs. Using this procedure, they found that older adults took 1.90 times as long per item as young adults.…”
Section: Discussionmentioning
confidence: 99%
“…& Somberg, 1982), and a number of recent studies have explored this difference by applying the diffusion model (e.g., Ratcliff, Thapar, Gomez, & McKoon, 2004). This model assumes that evidence accumulates over time until it reaches one of two decision boundaries (e.g., "studied" versus "not studied" in a recognition memory task).…”
mentioning
confidence: 99%